Charles E. Bohlen papers - Bohlen, Charles E. (Charles Eustis), 1904-1974.; Bohlen, Charles E. (Charles Eustis), 1904-1974.
Correspondence, speeches, lectures, writings, notes, research material, interviews, subject files, appointment books, photograph albums, photographs, and other papers relating primarily to Bohlen's diplomatic career. Includes drafts of his book Witness to History, 1929-1969 (1973) and speeches given by Bohlen during his ambassadorships to France, the Philippines, and the Soviet Union on subjects such as foreign policy and relations between the U.S. and Soviet Union. Also includes official logs of trips by presidents Franklin D. Roosevelt and Harry S. Truman to the Yalta Conference and to Berlin, Germany, in 1945; typescripts of addresses given by Dean Acheson; material pertaining to peace conferences held during and after World War II and to a visit to Japan and South Korea; and biographical material pertaining to Bohlen's grandfather James B. Eustis.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Diplomat, executive, and author. Nickname: Chip.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Acheson, Dean, -- 1893-1971.; Eustis, James B. -- 1834-1899.; Roosevelt, Franklin D. -- 1882-1945.; Truman, Harry S., -- 1884-1972.; Diplomatic and consular service, American -- France; Diplomatic and consular service, American -- Philippines; Diplomatic and consular service, American -- Soviet Union; World War, 1939-1945 -- Diplomatic history; World War, 1939-1945 -- Peace; Berlin (Germany) -- Description and travel; France -- Foreign relations -- United States; Japan -- Description and travel; Philippines -- Foreign relations -- United States; South Korea -- Description and travel; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- France; United States -- Foreign relations -- Philippines; United States -- Foreign relations -- Soviet Union; Soviet Union -- Foreign relations -- United States; Authors; Executives; Diplomats